KAJIAN LITERATUR TENTANG PENERAPAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MENULIS KARANGAN NARASI SISWA DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Yuni Fadhilah; Yoyo Zakaria Ansori; Budi Febriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze research trends and aspects of improvement in elementary school students’ narrative writing skills through the implementation of Problem Based Learning (PBL). The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Data sources were obtained from Google Scholar and Scopus, covering publications from 2021 to 2026. After the selection process, 12 articles were included and analyzed qualitatively. The results indicate that research on PBL is predominantly conducted using Classroom Action Research (CAR) methods and is frequently combined with learning media such as picture series, audiovisual media, and flipbooks. The studies are also mainly focused on fourth-grade elementary school students. In addition, the most improved aspect of narrative writing skills is narrative structure, followed by idea development, creativity, language skills, and writing process. In conclusion, Problem Based Learning is effective in improving elementary students’ narrative writing skills in terms of both learning process and learning outcomes.